Granice mowy - KOT, Dobrosław (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The article presents the borderlands of speech, namely, those moments when the philosophical language encounters fundamental problems concerning expression. The borderline then is silence. The paper discusses four modi of silence: shame, perplexity, ignorance and mystery. Their analysis points to the need to transgress the borders of the unequivocal and precise language. Such a necessity appears already in the question itself the human being poses about what lies beyond the borders: the human being asks this question, and while asking, opens a certain perspective. Subsequently, two significant attempts at transgressing the borders of language are characterized, namely, the ones proposed by, respectively, Martin Heidegger and Martin Buber. Both philosophers were striving to describe the reality and experience that escape the possibility of discursive description, discursive language being one «about something,» as opposed to Heidegger’s and Buber’s key concepts, namely, “being” and “You”. Thus the article attempts to discover the methods by means of which both philosophers attempted to speak about what is difficult or utterly impossible to talk about. Translated by Dorota Chabrajska